Impact of 1,25(OH) 2 D 3 on TG content in liver of rats with type 2 diabetes - Yang,Yan (2018)
Abstract Purpose: To evaluate the effects of 1,25 dihydroxy vitamin D3 (1,25(OH)2D3) on the content of triglyceride (TG), as well as on the gene and protein expressions of adiponectin receptor 2 (AdipoR2), p38 mitogen-activated protein kinase (P38MAPK), and lipoprotein lipase (LPL) in the liver of rats with type 2 diabetes mellitus (T2DM) so as to provide theoretical basis for exploring the mechanism by which 1,25(OH)2D3 regulates TG. Methods: Wistar rats were divided into four groups (n=25), with different treatments and detected the gene and protein expressions of AdipoR2, p38MAPK, and LPL in the liver tissue by reverse transcription polymerase chain reaction (RT-PCR) and Western blotting. Meanwhile, the content of TG in the liver tissue was detected by the Enzyme-linked immunosorbent assay. Results: The expression of AdipoR2, p38MAPK, LPL gene and protein in the liver of VitD intervention group was significantly higher than that in T2DM group (P <0.05), while the TG content was significantly lower than that in T2DM group (P <0.05). Conclusion: 1,25(OH)2D3 can decrease the content of TG in the liver, and its mechanism may be achieved by upregulating the expressions of AdipoR2, p38MAPK, and LPL in the liver.